Estudo morfológico das formas verbais do modo imperativo nas Cantigas de Santa Maria - Fávaro, Gisela Sequini [UNESP] (2016)
This study aims to map and analyze the morphological structure in the process of verb inflection of imperative forms in Archaic Portuguese (AP) in the Cantigas de Santa Maria (CSM). The objective of the study is to show if the situation we find today (i.e., variation among indicative and subjunctive forms to express orders and requests), which leads to the question if the imperative was an independent mood or not, already occurred in the AP. The methodology consists in mapping the imperative verb forms in the CSM. We have also used glossaries and vocabularies as a support in categorization of verb forms. After data is collected, the morphological structure of the imperative verb forms found are analyzed in comparison with the morphological structure of the simple present and subjunctive mapped in the corpus, in order to explain if criteria, such as order, presence or absence of the subject and contexts related to speech acts (order or request), can be used to consider if a form is imperative or not. One hundred eighty-nine imperative verb forms conjugated in the secondperson plural and second-person singular were collected and at the end of the analysis of the data we verified the high productivity of the suppression of the thematic vowel at an early stage of the language. We can prove that the imperative form preserved its morphological structure in the AP, since the variation indices start to emerge only in mid-eighteenth century, when there are the first manifestations of the process which replaces tu by você in treatment relations. We have also discussed, from a diachronic perspective, by the factors of linguistic and social nature that interfered and continue to interfere in the process of change in pronoun forms of address in BP and how this phenomenon is associated with the probable loss of the morphology of the imperative form. Thus, this thesis aimed to contribute to the history of the Portuguese language, considering that the resumption of facts of the linguistic past of the Portuguese language can bring greater understanding of the structure of the current Portuguese.